2020
DOI: 10.1111/1365-2664.13699
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐offs between biodiversity and agriculture are moving targets in dynamic landscapes

Abstract: 1. Understanding how biodiversity responds to intensifying agriculture is critical to mitigating the trade-offs between them. These trade-offs are particularly strong in tropical and subtropical deforestation frontiers, yet it remains unclear how changing landscape context in such frontiers alters agriculture-biodiversity trade-offs. 2. We focus on the Argentinean Chaco, a global deforestation hotspot, to explore how landscape context shapes trade-off curves between agricultural intensity and avian biodiversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 47 publications
4
25
1
Order By: Relevance
“…These data support previous studies highlighting a need to account for the effects of isolation from natural habitat when considering agricultural policies for biodiversity protection (Batáry et al, 2011;Gilroy et al, 2014;Macchi et al, 2020;Zhang et al, 2017) and underline that in tropical regions, failing to account for the importance of large tracts of natural habitat within the landscape may lead to incorrect conclusions about the biodiversity benefits of land-sharing agriculture and hence to inappropriate land management strategies.…”
Section: Discussionsupporting
confidence: 86%
“…These data support previous studies highlighting a need to account for the effects of isolation from natural habitat when considering agricultural policies for biodiversity protection (Batáry et al, 2011;Gilroy et al, 2014;Macchi et al, 2020;Zhang et al, 2017) and underline that in tropical regions, failing to account for the importance of large tracts of natural habitat within the landscape may lead to incorrect conclusions about the biodiversity benefits of land-sharing agriculture and hence to inappropriate land management strategies.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, there is considerable doubt if silvopastoral systems, as currently practiced, will maintain environmental values in the long-term; with evidence that they rapidly loose trees and carbon (Fernández et al, 2020). Likewise, biodiversity found in silvopastures might heavily depend on nearby forests (Macchi et al, 2020), and silvopastures might constitute sink habitat as hunting pressure on them can be high (Romero-Muñoz et al, 2020). All this cautions against a widespread expansion of silvopasture into remaining forests (as encouraged by the current zoning), and our results suggest rather that areas currently under intense agricultural land systems are converted to silvopasture.…”
Section: Discussionmentioning
confidence: 99%
“…forest, cropland, pasture, natural grasslands, and other). Silvopastoral systems were identified as pastures with 12-30% woody cover (Macchi et al, 2020).…”
Section: Land Systems and Their Current And Potential Benefitsmentioning
confidence: 99%
“…Beyond these studies, one abundance‐based analysis (lacking yield data) has concluded sparing probably outperforms sharing for birds in a Bornean forest/oil palm landscape (Edwards et al ., 2010). Two more recent studies that have used density measures have highlighted the value, within agricultural landscapes, of retaining forest blocks (Karp et al ., 2019) or woodlands (Macchi et al ., 2020), but do not consider the consequences (if these are to be safeguarded while production is to be sustained) of maintaining high yields elsewhere.…”
Section: Sharing and Sparing In Agriculturementioning
confidence: 99%